Pengaruh Jiwa Zaman dan Latar Belakang Penulis Dalam Dua Karya Novel: Laut Bercerita dan Dua Batang Ilalang - Ayuni Rianty; Etmi Hardi (Jurnal Kronologi, 2020)
Explanation of the events regarding the Student Movement in the novel Dua Batang Ilalang by Wahjoe Sardono and Laut Bercerita by Leila S Chudori, it is necessary to do a review or interpretation of whether the background and soul of the era influenced the exposure in the novel. This study aims to describe the influence of the mental condition of the age and the background of the author on the portrayal of the student movement in his work. Researchers apply a historiographic approach, using the method of library research with text or document data sources. Four stages: First, prepare supporting objects such as stationery. Second, the collection of works (bibliography) relating to the student movement, New Order and novel writers in the form of hardcopy and softcopy. Third, time management. Fourth, read and make note of results. The results of the study are: (1) Background of the writer, Leila S. Chudori is a writer since childhood, when he grew up he became a journalist for Tempo magazine. Wahjoe Sardono is a well-known comedian in Indonesia, and several other professions that he was involved in. (2) The Condition of the Soul of the Age, Storytelling Sea: 2017. Social and political conditions at that time were more democratic which gave freedom to the writers. Two Batang Ilalan: 1999. The transitional period of reform caused limitations and restraints on the author. The background causes different perspectives and special characteristics on the author's presentation in his work. While the soul of the times influences the limitations and freedom of imagination and language style as outlined.